Efficiency of Life Conveyor Manufacturing Project Completion Time Using Critical Method Path Method at CV. Mabar Karya Utama - Jaka Maulana; Vidi Agung Fragastia (Industrial Engineering System and Management Journal, 2025)
The project for the creation of the Life Conveyor at CV. Mabar Karya Utama is a strategic initiative aimed at enhancing operational efficiency and the company's competitiveness in the manufacturing industry. In the execution of this project, there are several key problems related to delays in completion and time management, which ultimately affect operational costs and production schedules. To address these issues, this research utilizes the Critical Path Method (CPM) as an analytical and planning tool to identify critical activities that determine the duration of project completion. The research is conducted using a case study approach at CV. Mabar Karya Utama through the collection of both primary and secondary data. Primary data is obtained through in-depth interviews with the project managers, technicians, and operational staff, while secondary data is collected from internal documentation and previous project reports. Data analysis is performed by constructing a project network diagram that illustrates the relationships between activities and identifies the critical path that has no time slack. As a result, any delays in activities that fall within the critical path can directly impact the overall project duration. The analysis results indicate that the application of the CPM method can pinpoint weaknesses in the initial planning, such as suboptimal resource allocation and the lack of synergistic coordination between departments. With this identification, management can efficiently take corrective actions, such as redistributing resources and establishing more appropriate activity priorities. Furthermore, the use of CPM also allows for real-time monitoring of project progress, enabling proactive implementation without frequent dialysis. The conclusion of this study states that the Critical Path Method has proven effective in enhancing the efficiency of project completion time for the Life Conveyor creation at CV. Mabar Karya Utama. The application of CPM not only aids in schedule control but also provides a clearer picture of the workflow process and identifies obstacles encountered during implementation. Thus, it is hoped that the company can apply the findings from this research as a foundation for future project management improvements, thereby increasing productivity and positively impacting the overall performance of the company. From the results of a study, several results can be concluded, namely: 1) The critical path method (CPM) can be applied in the Life Conveyor manufacturing project at CV Mabar Karya Utama by identifying project activities, as well as determining the sequence of work again, calculating the completion time of each task, and finding the critical path that determines the minimum project time. 2) There are 11 critical paths that affect the progress of this project A1 + B1 + B2 + B3 + B4 + F1 + F2 + G1 + H1 + H2 + I1 and the path that has the most influence is when paths B3 and B4 are accelerated for 4 days. 3) The project completion time was 27 days with a total crashing cost of Rp. 309,545,750., - with an optimization level of acceleration of work time of 12.96%.